The Future of Global Economic History. Regional Comparisons to Address Global Questions - De Zwart, Pim (TSEG - The Low Countries Journal of Social and Economic History, 2018)
Economic history deals with the process of economic development across the globe in the long-run. In this essay, I put forth ideas about what economic historians should be doing in the next 10 years in terms of content, methodology and the scale of analysis. In terms of content, I suggest that prospective research questions should generate what I consider ‘useful knowledge’ and provide two example topics: inequality and globalization. Regarding methodology I argue in favour of the comparative (quantitative) method in order to analyse processes of change in a variety of contexts. The scale of analysis should refocus from the country to the regional level in order to be better able to tease out relevant relationships in a comparative analysis.